Literasi Masyarakat dan Pengentasan Buta Aksara: Kebijakan Pemerintah dalam Merealisasikan SDGs Quality Education di Kabupaten Sumenep - Wilda Rasaili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The alleviation of illiteracy in Indonesia has been performed by the central government through the district government policy. In this study will be performed a research about the alleviation of illiteracy in Sumenep district by using paradigm of SDGs (Sustainable Development Goals) in quality educational aspect and skill life education. This research uses descriptive-qualitative method in collecting and analyzing the data about the alleviation of illiteracy policy that is applied by government in Sumenep district. The Sumenep district government policy becomes a basic part in advancing the society, includes the policy in education aspect. One of the Sumenep district’s policies in education aspect includes an initiation in convincing the society through the alleviation of illiteracy for poor people. This research gets a conclusion that alleviation of illiteracy was performed by Sumenep district government in order the people get the quality education for their development in literary aspect (reading and writing) and to support their future that is faced to the technology world more advanced and more advanced, this becomes an indicator of prevailed policy.